(untitled) (Journal of Innovation in Academia, 2025)
This article explores the syntactic parallelism in Mulan. The selected sentences were analyzed on the basis of structure, functions and voice. Most of the Nepali active voices in the source text (ST) have been translated into English active voices in the target text (TT). Therefore, the tendency of active (ST) into active (TT) was very high. Similarly on the basis of sentence types, simple sentences in the ST translated into simple sentences in the TT has higher tendency as compared to compound sentences in the ST translated into compound sentences in the TT. The complex sentences in the ST translated into complex sentences in the TT have highest tendency. Likewise on the basis of sentence function, the declarative sentences in the ST into declarative sentences in the TT has highest tendency. Interrogative sentences in the ST into interrogative sentences in the TT has higher tendency than exclamatory sentences.